Arus Kas Operasi, Laba Operasi, Return On Equity Dan Harga Saham Perusahaan Food And Beverage Yang Terdaftar Di Bursa Efek Indonesia - Hotman Fredy; Amelia Aji Kusumadewi (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2015)
This research to determine the influence of Operation Cash Flow, Operating Income and Return on Equity (ROE) on Equity Shares for the food and beverage companies in Indonesian Stock Exchange. The data used in this study is secondary data by purposive sampling method. The number of samples used by 13 companies using multiple regression analysis. This results indicate that all independent variables simultaneously is Operating Cash Flow, Operating Income and Return On Equity significant influence on stock prices. The test results showed only partial Return On Equity significantly the stock price. As for Operating Cash Flow and Operating Income are not significantly influence the stock price.